2015
DOI: 10.1080/10934529.2015.1038181
|View full text |Cite
|
Sign up to set email alerts
|

Removal of cationic dye methylene blue by zero-valent iron: Effects of pH and dissolved oxygen on removal mechanisms

Abstract: Effects of pH and dissolved oxygen on mechanisms for decolorization and total organic carbon (TOC) removal of cationic dye methylene blue (MB) by zero-valent iron (ZVI) were systematically examined. Decolorization and TOC removal of MB by ZVI are attributed to the four potential mechanisms, i.e. reduction, degradation, precipitation and adsorption. The contributions of four mechanisms were quantified at pH 3.0, 6.0 and 10.0 in the oxic and anoxic systems. The maximum efficiencies of decolorization and TOC remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 46 publications
(100 reference statements)
1
21
0
1
Order By: Relevance
“…This phenomenon can further contribute to the decolorization of AO7 due to the anionic characteristic of AO7 under the examined conditions. Thus, coagulation/flocculation and adsorption processes are involved for the decolorization of AO7 in mFe/Cu‐BPs system, where similar phenomena were reported for the degradation of methylene blue and chromium . On the other hand, when the initial pH was further increased from 6.5 to 8.0, the decolorization efficiency and k obs significantly declined to 85.47% and 0.0660 min −1 ( R 2 =0.9922), respectively.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…This phenomenon can further contribute to the decolorization of AO7 due to the anionic characteristic of AO7 under the examined conditions. Thus, coagulation/flocculation and adsorption processes are involved for the decolorization of AO7 in mFe/Cu‐BPs system, where similar phenomena were reported for the degradation of methylene blue and chromium . On the other hand, when the initial pH was further increased from 6.5 to 8.0, the decolorization efficiency and k obs significantly declined to 85.47% and 0.0660 min −1 ( R 2 =0.9922), respectively.…”
Section: Resultssupporting
confidence: 67%
“…Similar results at different Fe/Cu-BPs dosage have also been reported for the removal of Acid Red 73 [9], AO7 [11], pnitrophenol [12], and nitrobenzene [13]. These phenomena may be attributed to two reasons: (1) when the range of mFe/Cu-BPs dosage was up to 45 g/L, the total surface area and catalytic sites on the surface of mFe/Cu-BPs increases, enhancing both mass transport rates of intermediates between the solution phase and the mFe/Cu-BPs surface and facilitating the generation of infinite galvanic cells [11,14,31,35]; (2) when the range of mFe/Cu-BPs dosage > 45 g/L, the mass transfer rate dictates the overall process, rather than mFe/Cu-BPs dosage. In other words, mass transfer rates of AO7 and its intermediates will be suppressed considerably due to overloading the system, and thereby negatively impacting k obs [36][37][38].…”
Section: Effect Of Mfe/cu-bps Dosage On the Decolorization Of Ao7mentioning
confidence: 99%
“…Hydrazine is toxic to human and environment, as well as nitrification microorganisms [13]. OH* radical has been used to remove chemical toxic pollutants [14], [15]. Sun suggested that application of nZVI was a good technology in decolorization of cationic dye methylene blue [14].…”
Section: Introductionmentioning
confidence: 99%
“…OH* radical has been used to remove chemical toxic pollutants [14], [15]. Sun suggested that application of nZVI was a good technology in decolorization of cationic dye methylene blue [14]. Bremner investigated the degradation of the model pollutant phenol with hydroxyl radicals generated from zerovalent iron and hydrogen peroxide [15].…”
Section: Introductionmentioning
confidence: 99%
“…Fe 0 is a promising reactive medium because it is readily available at low costs and has low toxicity . Moreover, it can be easily separated from the solution with a simple magnetic process, which shows its superiority to Fe 2+ . Compared with the traditional Fenton process, the amount of iron ions in the solution in the AFP can be reduced by 50% so that iron sludge is significantly reduced …”
Section: Introductionmentioning
confidence: 99%